Testing the psychometric properties of the risk-rescue rating scale: a lethality measure for suicide attempts - Tormod Stangeland; Ketil Hanssen-Bauer; Johan Siqveland (International Journal of Mental Health Systems)
Abstract Health personnel lack a common standard for assessing lethality of suicide attempts. This may lead to inconsistent assessments and unclear reports about suicide attempts. We argue that the Risk-Rescue Rating Scale (RRRS) may help in resolving this problem. It is a measure based on observable indications of the medical danger of a suicide attempt and of the patient’s efforts to avoid or achieve rescue. The instrument is a clinician-rated supplement to self-reports and can be administered in a few minutes and learned in a single brief teaching session. We adapted the RRRS for contemporary use in a Norwegian acute adolescent mental health service clinic. We developed a training program for clinicians, a user manual, and a series of five video-based role-played interview cases for reliability testing. In this study, we recruited 28 clinicians with professional backgrounds typical of Norwegian mental health personnel. They rated five role-played video interviews using the RRRS and the well-established interview instrument the Suicide Intent Scale (SIS) and obtained 140 sets of scores. We estimated the interrater reliability (intraclass correlation coefficient [ICC]) to be .93 for the RRRS and .94 for the SIS, both excellent levels. Correlation was .80 between the RRRS and SIS items that were similar to the RRRS and .53 for SIS items measuring other topics, indicating good concurrent and discriminant validity. Adopting a common standard for communicating about suicide attempts can improve clinical practice, and the RRRS may prove to be a reliable and practical candidate for this task.